The relationship between psychiatric nurses’ perceived organizational support and job burnout: Mediating role of psychological capital - Tang, Yingxue; Wang, Yingxuan; Zhou, Haiying; Wang, Juan; Zhang, Rui; Lu, Qinghua (Frontiers in Psychology, 2023)
Background Psychiatric nurses need to keep close contact with patients suffering from mental illness. Because of the special nature of their profession, there is an increasing incidence of job burnout among psychiatric nurses. Aim This study examined the relationship between psychiatric nurses’ perceived organizational support, job burnout, and psychological capital. It also investigated the mediating role of psychological capital in the relationship between their perceived organizational support and job burnout. Methods A total of 916 psychiatric nurses were recruited from 6 grade-III mental facilities in Shandong Province using the stratified sampling approach. Their data were collected and examined using a general demographic data questionnaire, The Maslach Burnout Inventory, the Perceived Organizational Support Scale, and the Psychological Capital Questionnaire. Results The total score of job burnout was 53.71 ± 16.37. Specifically, 73.69% of the nurses had moderate to severe emotional exhaustion, 76.75% had moderate to severe job burnout pertaining to depersonalization, and 98.80% had moderate to severe job burnout pertaining to personal accomplishment. Spearman’s correlation analysis showed that both psychological capital (r = −0.35, p < 0.01) and perceived organizational support (r = −0.31, p < 0.01) were adversely related to job burnout. Additionally, psychological capital somewhat mediated the relationship between perceived organizational support and job burnout. Its mediating impact accounted for 33.20% of the overall effect. Conclusion This study’s participants had a moderate to severe level of job burnout. However, organizational support and psychological capital can be crucial in alleviating this problem among psychiatric nurses. Therefore, nursing managers and medical institutions should undertake timely and positive interventions to improve psychiatric nurses’ mental health and prevent job burnout. While exploring the impact of organizational support and psychological capital on job burnout, future studies should consider other effective influencing factors, and the relationship between the different factors should be explored in depth. This would provide a basis for developing a job burnout prevention mechanism.